Relationship of Sedentary Lifestyle With Hypertension Incidence in Productive Ages (20-59 Years) Among Educators and Educational Staff in Jember, Indonesia - Qaimima Ayuni; Citra Anggun Kinanthi; Irma Prasetyowati (Association of Public Health Scholars based in Faculty of Public Health, Sriwijaya University, 2024)
Hypertension remained a major global health issue that had not been fully addressed, causing 10.8 million deaths and serving as the leading risk factor for mortality worldwide. A sedentary lifestyle was a significant contributor to hypertension among the productive age group. It had been shown that a sedentary lifestyle decreased Nitric Oxide (NO) levels, cardiac output, and systemic blood flow, which altered blood vessel diameter, reduced insulin sensitivity, and impaired vascular function. These factors negatively impacted cardiovascular health, including the development of hypertension. The prevalence of hypertension among university educators was higher compared to other educational institutions, primarily due to lower physical activity levels and greater career pressures. Therefore, the objective of this research was to analyze the relationship between a sedentary lifestyle and the incidence of hypertension in productive ages among educators and educational staff in Jember. This research was a quantitative analytic study with a cross-sectional approach. The population of the study consisted of 2,531 educators and educational staff in Jember. A sample of 106 respondents was selected through simple random sampling. Data collection was conducted through interviews and the use of a Global Physical Activity Questionnaire (GPAQ). Both bivariate and multivariate analyses employed binary logistic regression. The results of the bivariate analysis showed significant associations between hypertension and characteristics such as age, family history of hypertension, smoking, Body Mass Index (BMI), and sedentary lifestyle (p-value < 0.05). However, gender was not significantly associated with hypertension (p-value > 0.05). The multivariate analysis confirmed that a sedentary lifestyle was the most dominant determinant of hypertension.